Case Report: A Composite Diffuse Large B-cell Lymphoma and Classic Mantle Cell Lymphoma in the Small Intestine - Hadwani, MBBS*, Ruhi; Lavergne, MD, Jessica; Aftab, MD, Lalarukh (North American Journal of Medicine and Science, 2025)
Composite lymphomas, defined as the coexistence of two distinct lymphoma subtypes within the same tissue, are rare entities, comprising only 1–4.7% of all lymphomas. Among these, the concurrent occurrence of diffuse large B-cell lymphoma (DLBCL) and mantle cell lymphoma (MCL) is exceedingly rare, with only a handful of cases reported. Accurate diagnosis and tailored treatment are critical given the distinct biological and clinical behaviors of these lymphomas. Here, we report the case of a 71-year-old male with a history of Crohn’s disease, presenting with a mass involving the ileocecal valve and terminal ileum, revealed on imaging and confirmed via right hemicolectomy and small bowel resection. Histopathological analysis identified two adjacent but immunohistochemically distinct lymphomas: a classical MCL with nodular architecture and a high-grade DLBCL. Immunohistochemistry and fluorescence in situ hybridization (FISH) studies demonstrated that the MCL expressed SOX11, Cyclin D1, and CD5, with CCND1/IGH translocation present, while the DLBCL lacked these markers, confirming the two lymphomas were clonally unrelated. This case represents the first reported composite lymphoma of MCL and DLBCL arising in the small intestine. The distinction between these two lymphomas was achieved through a combination of morphological, immunohistochemical, and genetic analyses. The rarity and heterogeneity of composite lymphomas pose diagnostic and therapeutic challenges, emphasizing the need for comprehensive evaluation. Given the aggressive nature of DLBCL, treatment often prioritizes this component, although the individualized management of composite lymphomas remains essential. This case highlights the importance of thorough diagnostic workup, including advanced immunohistochemistry and genetic studies, to differentiate between lymphoma subtypes within composite lymphomas. Excisional biopsy remains critical to minimize sampling bias, and further research is needed to understand the pathogenesis and optimize treatment strategies for these rare entities. [N A J Med Sci. 2024;18(1):001-004. DOI: 10.7156/najms.2024.1801001]